Analysis on the Plot of Short Story "Soldier's Home" By Ernest Hemingway - JMMatai PSDKU; Anton Magelang (MATAI: International Journal of Language Education, 2021)
The title of this study is AN ALYSIS ON THE PLOT OF SHORT STORY "SOLDIER'S HOME" BY ERNEST HEMINGWAY. The aim of this study is to find out the Plot used in the Short story â€œSoldierâ€™s Homeâ€. The researcher applied Descriptive study method, aim analyzing and describing the data. The data of the study is Short story "Soldier's Home" by Ernest Hemingway. From the result, the researcher analyzed the plot of short story "Soldier's Home" by using Descriptive analysis. The researcher found out that, parts of plot used in the story "Soldier's Home" is: Exposition which tells about the introduction of Krebs as main character who is a Soldier of United States. He takes a part in the World War 1 in 1917 in Europe. Complication tells about the experience of the war changes his attitude toward work and woman after he comes back to his town Oklahoma - a town in United States. Crisis or climax tells the complications become more developed where there is a contradiction of the idea about work and woman among Krebs and his Parents. This is the high point of the story, Falling action tells about the action of Krebs falls where he becomes aware of his changes attitude that caused by the experience of the war and he tries to be a good boy to his mother, Resolution tells that Krebs accepts parents suggestion where he has forgotten the experience of the war that influence him in the town and he has decided to find out another job in Kansas- United States that can makes him enjoy it. The findings presented in this writing are still open to be proved by other.